2008
DOI: 10.3928/01477447-20110414-18
|View full text |Cite
|
Sign up to set email alerts
|

Suture Anchor Versus Suture Through Tunnel Fixation for Quadriceps Tendon Rupture: A Biomechanical Study

Abstract: This biomechanical study compared suture anchors versus transosseous sutures for repair of quadriceps tendon ruptures using a force of 150 N at a frequency of 0.5 Hz. No significant difference in displacement was found between the 2 techniques with initial loading or with load or no load after 1000 cycles. Displacement after 1000 cycles for suture anchors and bone tunnels was 4.65 and 4.50 mm, respectively. These findings suggest a possible role for suture anchors in repairing quadriceps tendon ruptures. Sutur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 6 publications
0
62
1
7
Order By: Relevance
“…Hart investigated biomechanical differences between trans-osseous equivalent double-row suture anchor and trans-osseous tunnel repair: he reported that both were effective in terms of strength, repair stiffness and gap formation with similar results, but the transosseous repairs were stronger 28 . Lighthart et al found no significant differences in terms of displacement after 1000 cycles, adding that suture anchors are more expensive but, as confirmed also by Richards et al 24 , Maniscalco et al 25 and Bushnell et al 26 , allow a smaller skin incision and reduce operative times 29 . For delayed repair and re-ruptures are suggested Scuderi technique 4 to reinforce and Codivilla technique to lengthen the tendon.…”
Section: Quadriceps Tendon Tear Rupture In Healthy Patients Treated Wmentioning
confidence: 89%
“…Hart investigated biomechanical differences between trans-osseous equivalent double-row suture anchor and trans-osseous tunnel repair: he reported that both were effective in terms of strength, repair stiffness and gap formation with similar results, but the transosseous repairs were stronger 28 . Lighthart et al found no significant differences in terms of displacement after 1000 cycles, adding that suture anchors are more expensive but, as confirmed also by Richards et al 24 , Maniscalco et al 25 and Bushnell et al 26 , allow a smaller skin incision and reduce operative times 29 . For delayed repair and re-ruptures are suggested Scuderi technique 4 to reinforce and Codivilla technique to lengthen the tendon.…”
Section: Quadriceps Tendon Tear Rupture In Healthy Patients Treated Wmentioning
confidence: 89%
“…[1][2][3][4][5]12,17,19 The standard of care is passage of nonabsorbable sutures through transosseous patellar bone tunnels, but repair with suture anchors has been studied as an alternative that allows for less tissue trauma, decreased operative time, safe early initiation of rehabilitation protocols, and reduced risk of patella fracture or damage. 3,7,[10][11][12][18][19][20]21,23 Despite these potential advantages, biomechanical studies have yielded inconsistent results regarding the superiority of suture anchor repair over repair with transosseous tunnels. 7,[10][11][12][18][19][20] We propose quadriceps tendon repair using the 4.75-mm biocomposite knotless suture anchor with tape suture technique as a biomechanically superior alternative to either transosseous tunnels or suture anchor repair alone, with significant advantages both in and out of the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]8,9 The standard of care is repair with a nonabsorbable suture passed through transosseous patellar tunnels, often with several weeks of postoperative immobilization to protect the repair. 3,4,7,[10][11][12] Reported complications of this method include significant extension lag, decreased strength, and ROM compared with the contralateral knee, chronic pain, and iatrogenic patellar fracture. 8,[13][14][15][16][17][18] Repair techniques using suture anchors have been proposed as viable alternatives, but biomechanical studies comparing them with standard transosseous repair have reported mixed results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[16] compared the biomechanical strength between bone tunnel repair and suture anchors. They found no statistical difference in mean initial displacement after 10 cycles between suture anchor and bone tunnel repairs on the lateral or medial side.…”
Section: Discussionmentioning
confidence: 99%